Persepsi Masyarakat Terhadap Pemilihan Bank Syariah - Hurian Kamela; Evony Silvino Violita; Miranti Kartika Dewi (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The purpose of this study is to study the views of the public who use conventional banks compared to Islamic Banks, also to give an assessment to the public about the choice of bank choice, to give an overview of making decisions related to people related to the selection of Islamic Banks, and to find reasons that support Indonesian people to choose a Sharia Bank. This research using questionnaire data of 126 people. The main points of this study consist of ability, attention, religious reasons (independent variable) and Consent (dependent variable). The outline of the results of this study is enough to study respondents' assessments of Islamic banks, for the highest relationship, on average many focus on questions on X2, Attention in the questionnaire are: Conventional banks are better than Sharia banks, The government must support Sharia banks, Facilities about Sharia Banks must be added, Sharia Bank Coverage (example: ATM) must added. This is the highest focus on the respondent in the view of Islamic banks on other questions.